QUALITY ASSESSMENT OF LOCALLY PRODUCED HONEY FROM USMANU DANFODIYO UNIVERSITY, SOKOTO - Shehu, Abdulkadir; Bandiya , H.M.; Umar , Aisha; Shehu, Zulkallaini (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2022)
This study is conducted to analyze and compare the physico-chemical properties and mineral compositions of locally produced honey samples in Usmanu Danfodiyo University Sokoto with the national and international standards. To achieve these, seven samples of locally produced honey was collected from the study area. the physicochemical properties was analysed using the Official Methods of Analysis established by Association of Official Analytical Chemists while the mineral compositions of all the honey samples were determined using flame photometer and atomic absorption spectrophotometer. The results showed that the colours ranged from extra light amber to light amber; electrical conductivity from 0.06±0.01mS/cm to 1.15±0.16mS/cm and density from 1.41±0.00g/cm3 to 1.36±0.00g/cm3. On the mineral composition, the ash content was from 0.08±0.00% to 0.18±0.01%; moisture content from 3.94±0.29mg to 20.29±0.20%; total reducing sugars from 63.23±2.46% to 73.34±2.77%; free acidity from 14.48±0.53meq/kg-1 to 37.38±1.12meq/kg-1; lactonic acidity from 9.50±2.00meq/kg-1 to 15.50±1.50meq/kg-1; total acidity from 25.7±2.53 meq/kg-1 to 47.58±1.12 meq/kg-1. The physico-chemical and mineral compositions of the honeys were found to meet the established national standards. It was thus, concluded that honey from the area of study are of good quality